A case report of dipeptidyl peptidase 4 inhibitor-related kidney disease combined with renal cancer - Kurihara, Shigekazu; Sawa, Naoki; Sumida, Keiichi; Ikuma, Daisuke; Oba, Yuki; Mizuno, Hiroki; Sekine, Akinari; Yamanouchi, Masayuki; Hasegawa, Eiko; Suwabe, Tatsuya; Urakami, Shinji; Kono, Kei; et al. (Frontiers in Nephrology, 2024)
A kidney biopsy was performed in a 64-year-old woman with type 2 diabetes mellitus and less than 1 g of proteinuria who rapidly progressed to end-stage renal failure after approximately 2 years of treatment with two dipeptidyl peptidase 4 (DPP-4) inhibitors for type 2 diabetes mellitus. The biopsy revealed not only a coincidental diagnosis of renal cell carcinoma, which was not evident on pre-biopsy computed tomography, but also severe thrombotic microangiopathy (TMA)-like glomerular endothelial cell damage in the noncancerous areas. These results suggest that DPP4 inhibitors may have been involved in two kidney diseases.